1998
DOI: 10.1063/1.121940
|View full text |Cite
|
Sign up to set email alerts
|

Molecular level alignment at organic semiconductor-metal interfaces

Abstract: In order to clarify the electronic structure of metal-molecular semiconductor contacts, we use photoemission spectroscopy to investigate the energetics of interfaces formed by vacuum deposition of four different molecular thin films on various metals. We find that the interface electron and hole barriers are not simply defined by the difference between the work functions of the metals and organic solids. The range of interface Fermi level positions is material dependent and dipole barriers are present at all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
284
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(297 citation statements)
references
References 15 publications
12
284
1
Order By: Relevance
“…show no dependence on dipoles at the metalorganic interface, which have opposite signs for PTCDA on Ag and Au [8]. The dipole at the PTCDA/Ag interface corresponds to electron transfer from the metal to interface molecules, which gives rise to the filled gap states at −0.6 and −1.8 eV on the 4Å UPS spectrum.…”
Section: Transport Gapmentioning
confidence: 99%
“…show no dependence on dipoles at the metalorganic interface, which have opposite signs for PTCDA on Ag and Au [8]. The dipole at the PTCDA/Ag interface corresponds to electron transfer from the metal to interface molecules, which gives rise to the filled gap states at −0.6 and −1.8 eV on the 4Å UPS spectrum.…”
Section: Transport Gapmentioning
confidence: 99%
“…1,2 These interface level alignments have been widely investigated in the last decade: since the SchottkyMott limit (where use of the vacuum level alignment is made) was disproved 3,4 many different mechanisms have been proposed to explain the barrier formation at MO interfaces: chemical reactions and the formation of gap states in the organic gap; 5-8 orientation of molecular dipoles; 9,10 or compression of the metal electron tails at the MO interface due to the Pauli repulsion. 7,[11][12][13] It has also been suggested that the tendency of the charge neutrality level (CNL) of the organic material to align with the interface Fermi level 14,15 plays also an important role; this mechanism is associated with the induced density of interface states (IDIS) and the charge transfer between the organic and the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Schottky-Mott model was disproved [11,12] by the observation of interface dipoles, several mechanisms have been proposed to explain the energy level alignment at organic interfaces: chemical reaction and the formation of gap states in the organic material [13]; orientation of molecular dipoles [14]; or compression of the metal electron tails at the MO interface due to Pauli repulsion [15,16]. Recently, some of us suggested [17] that an additional important mechanism is the tendency of the charge neutrality level (CNL) of the organic material to align with the metal Fermi level (at MO interfaces) or the CNL of the other organic material (at heterojunctions).…”
mentioning
confidence: 99%